Reliability of Arduino Serial Communication Systems: A Case Study on the Application of Cyclic Redundancy Check (CRC) - Raharjo, Budi; Wibowo, Mars Caroline (University of Science and Computer Technology, 2024)
In embedded systems, serial communication plays a crucial role in data transfer, particularly in Arduino-based projects. However, factors such as electromagnetic interference, noise, and signal degradation can compromise data integrity, leading to significant errors. Effective error detection systems are essential to ensure reliable data exchange. The Cyclic Redundancy Check (CRC) is one such method known for its ability to detect errors. Despite its potential, the practical application and impact of CRC on Arduino communication systems have not been extensively explored. This study implements CRC within Arduino serial communication by designing and developing software that integrates CRC for real-time error detection. The study rigorously tests this implementation in various scenarios to evaluate its performance, comparing data integrity with and without CRC. The results show that incorporating CRC significantly improves the reliability of data transmission in Arduino applications, enhancing error detection accuracy. This improvement strengthens existing systems and provides a solid foundation for developing more complex communication frameworks. The research advances reliable communication systems in embedded technologies. By demonstrating CRC's effectiveness in enhancing data integrity, the study offers valuable insights for developers and researchers seeking to improve serial communication across different applications.